THE INTERNET OF THINGS (IOT) IS REVOLUTIONARY FOR FUTURE TECHNOLOGICAL ADVANCEMENTS (Journal of Engineering and Health Sciences, 2022)
The internet of Things (IoT) is a new paradigm that has transformed the traditional way of life into ahigh-tech lifestyle. Smart cities, smart homes, pollution control, energy saving, smart transportation,smart industries are the changes caused by the IoT. Many important studies and researches have beendone to improve technology through IoT. However, there are still many challenges and problems thatneed to be addressed to achieve the full potential of the IoT. These challenges and problems must beconsidered from various aspects of IoT such as applications, challenges, possible technologies, socialand environmental impacts etc. The main purpose of this review article is to provide a detaileddiscussion from a technological and social perspective. This article discusses the various challenges andkey issues of the IoT, architecture and important application domains. The article also showcases theavailable literature and describes their contributions in various aspects of the IoT. Moreover, theimportance of big data and its analysis with respect to IoT has been discussed. This article will helpresearchers to understand the IoT and its application to the real world